THE EFFECT OF PHYSICAL THERAPY INTERVENTION AFTER CEREBELLAR RESECTION - Shalabi, Kholood M; Alabdulathim , Danah A.; Al-Taleb, Hanan M.; Almarzuqi, Raghad K.; Alsaleh, Dalal A.; Takroni , Manar A.; Alsaleh, Rahaf M.; Reem M.Basuodan (Journal of Ayub Medical College Abbottabad, 2024)
A variety of diseases, including gait ataxia, lack of coordination, diminished dexterity, and unsteady posture, can be brought on by cerebellar dysfunction. This case study looks into how a physical therapy program affected a 40-year-old patient’s dynamic balance after cerebellar tumour surgery. The patient complained of losing his balance and having uncoordinated motions on the left side of the body. The Timed Up and Go (TUG) test was used to gauge how the Frenkel coordination exercises and balance training affected dynamic balance following cerebellar tumour removal. The patient’s muscle strength in the left-side hip extensors, abductors and adductors, knee flexors and extensors, as well as the left-side shoulder, elbow, and wrist flexion and extension, significantly improved.